Performance of the most recent Microchannel-Plate PMTs for the PANDA DIRC detectors at FAIR - Krauss, Steffen; Böhm, Merlin; Gumbert, Katja; Lehmann, Albert; Miehling, Daniel; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Lehmann, D.; Peters, K.; Schepers, G.; Schwarz, C.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2023)
In the PANDA experiment at the FAIR facility at GSI two DIRC (Detection of Internally Reflected Cherenkov light) detectors will be used for π/K separation up to 4 GeV/c. Due to their location in a high magnetic field and other stringent requirements like high detection efficiency, low dark count rate, radiation hardness, long lifetime and good timing, MCP-PMTs (microchannel-plate photomultiplier) were the best choice of photon sensors for the DIRC detectors in the PANDA experiment. This paper will present the performance of some of the latest 2 × 2 inch 2 MCP-PMTs from Photek and Photonis, including the first mass production tubes for the PANDA Barrel DIRC from Photonis. Performance parameters like the collection efficiency (CE), quantum efficiency (QE), and gain homogeneity were determined. The effect of magnetic fields on some properties like gain and charge cloud width was investigated as well. Apart from that the spatial distribution of many internal parameters like time resolution, dark count rate, afterpulse ratio, charge sharing crosstalk and recoil electrons were measured simultaneously with a multihit capable DAQ system. The latest generation of Photonis MCP-PMTs shows a unexpected ”escalation” effect where the MCP-PMT itself produces photons.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Atomic layer deposition (ALD); DIRC; MCP-PMT; Microchannel-plate; PANDA; Photomultiplier